(untitled) (Nepalese Journal of Radiology, 2019)
Spontaneous rupture of mature cystic teratoma is a rare complication which results in leakage of the liquefied sebaceous contents into the peritoneum leading to acute or chronic peritonitis. We report a case of a 23-year-old female who presented with pain abdomen, abdominal distension and fever. Contrast enhanced abdominal CT scan showed right adnexal complex cystic lesion with discontinuity in its wall along with features of peritonitis.